MANAJEMEN ARDIMAN DALAM PENGELOLAAN SANGGAR TARI SAIYO SAKATODI KOTA PADANG - Andina, Alya; Wimbrayardi (Universitas Negeri Padang, 2025)
This study aims to understand and describe Ardiman Management in the management of the Saiyo Sakato Dance Studio in Padang City. This type of research is qualitative with a descriptive method. The main instrument in this study is the researcher themselves, assisted by writing tools, a camera and a voice recorder. Data is collected through literature review, observation, interviews and documentation. The steps to analyse the data are data reduction, data presentation and drawing conclusions. The results of the study show that Ardiman's management in managing the Saiyo Sakato Dance Studio in Padang City consists of planning, organising, actuating and controlling. Planning at the Saiyo Sakato Studio includes short-term and long-term programmes, with short-term programme planning involving regular practice, while long-term programmes are carried out over a period of one year and include overall organisational activity plans. The organisation of Sanggar Saiyo Sakato includes the leader, treasurer, secretary and coach. The activities of Sanggar Saiyo Sakato involve providing motivation, setting examples/role models and giving instructions. The supervision of Sanggar Saiyo Sakato includes internal control and external control. Internal control involves all management elements, primarily Mr Ardiman as the leader of the studio, while external control involves parties outside the management structure of Sanggar Saiyo Sakato who have cooperative relationships, such as the tourism office, educational institutions, and other relevant agencies.